Dianthus borbonicus (Caryophyllaceae), a new species from Sicily - Brullo, Salvatore; Brullo, Cristian; Colombo, Paolo; Galdo, Gianpietro Giusso Del; Ilardi, Vincenzo; Perrone, Rosaria (Phytotaxa, 2015)
Dianthus borbonicus a new species occurring in North-Western Sicily is described and illustrated. It is a rare chasmophyte belonging to the D. sylvestris group, which is exclusive of a rupestrian stand near Rocca Busambra (Ficuzza). Its macro- and micromorphological features (seed testa sculptures, and leaf anatomy), ecology, conservation status and a comparison with the related species are provided too.